Cluster headache prevalence: methodological considerations. A review of the literature - Torelli, P.; Castellini, P.; Cucurachi, L (Acta Biomedica Atenei Parmensis, 2006)
Cluster headache (CH), also known as “suicide headache”, is characterized by a distinctive periodic temporal pattern and by accompanying autonomic symptoms during the attacks. Epidemiological data for the general population are scarce: only five studies have been carried out until now on CH prevalence in the general population, with conflicting results (prevalence rates vary between 56 and 326 cases every 100,000 inhabitants). Recently, a study was performed to investigate a representative sample of the Italian general population aged over 14 years. Possible CH cases according to the diagnostic criteria of the 1988 International Headache Society (IHS) classification were screened out of a sample of 10,071 patients registered in the lists of seven general practitioners (GPs) in Parma, using a previously validated, specially designed self-administered questionnaire. The diagnosis of CH was confirmed in 21 subjects (nine women and 12 men). The estimated prevalence rate was 279/100,000 (95% CI: 173-427), 227/100,000 (95% CI: 104-431) in women and 338/100,000 (95% CI: 175-592) in men. Based on methodological considerations, we believe that a lifetime prevalence rate of 279/100,000 for a population aged over 14 years is a reliable figure and it is probably not much lower than in the whole general population, since some studies performed on large case series have shown that the onset of CH is not frequent under 14 years of age.